Cost-effectiveness of MR-mammography vs. conventional mammography in screening patients at intermediate risk of breast cancer - A model-based economic evaluation - Kaiser, Clemens G.; Dietzel, Matthias; Vag, Tibor; Froelich, Matthias F. (European Journal of Radiology, 2021)
Purpose: The aim of this study was to analyze the cost-effectiveness of screening patients of intermediate risk of breast cancer with MR-Mammography (MRM) versus conventional mammography (XM).
CRIS-Team WoS Importer:2021-03-26